Why inconsistency arguments fail: a response to Shaw. Issue 2 (3rd April 2022) - Blackshaw, Bruce P.; Colgrove, Nicholas; Rodger, Daniel
Abstract : Opponents of abortion are commonly said to be inconsistent in their beliefs or actions, and to fail in their obligations to prevent the deaths of embryos and fetuses from causes other than induced abortion. We have argued that these 'inconsistency arguments' conform to a pattern which is susceptible to a number of objections, and that consequently they fail en masse . In response, Joshua Shaw argues that we misrepresent inconsistency arguments, and that we underestimate the extent to which our opponents have anticipated and addressed counterarguments. In this essay we draw on aspects of Shaw's alternative formulation of inconsistency arguments to present an improved inconsistency argument structure. While we agree with Shaw that inconsistency arguments must each be examined on their merits, we reject Shaw's assertion that our objections are dependent on misrepresentations. Our initial objections remain largely successful, therefore, in dealing with the inconsistency arguments of which we are aware.